Dispersão e primeiro registro da espécie invasora kellicottia bostoniensis (Rotifera: Brachionidae) em dois reservatórios Brasileiros - De-Carli, Bruno Paes [UNESP]; de Albuquerque, Felícia Pereira [UNESP]; Bayanov, Nikolay Georgievich; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo Luiz Martins (Oecologia Australis, 2017)
Aquatic ecosystems are subjected to biological invasions which can causes imbalances mainly in the native populations. In most freshwater environments rotifers are abundant and highly adapted. The North American rotifer Kellicottia bostoniensis (Rousselet 1908) is widely distributed in Asia, Europe, North and South America inhabiting reservoirs, lakes and rivers of these continents. Here, the occurrence of K. bostoniensis is recorded for the first time in Atibainha and Cachoeira reservoirs (Cantareira System, Brazil). Dispersion mechanisms are discussed and this note extends the limit distribution of K. bostoniensis in São Paulo state.
Dispersion and first record of the invasive species kellicottia bostoniensis (Rotifera: Brachionidae) in two Brazilian reservoirs
Keywords: Exotic species; New occurrences; Range expansion; Zooplankton